Kinship, community, and self: essays in honor of David Warren Sabean - Coy, Jason Philip; Sabean, David Warren (Spektrum, 2015)
"David Warren Sabean was a pioneer in the historical-anthropological study of kinship, community, and selfhood in early modern and modern Europe. His career has helped shape the discipline of history through his supervision of dozens of graduate students and his influence on countless other scholars. This book collects wide-ranging essays demonstrating the impact of Sabean's work has on scholars of diverse time periods and regions, all revolving around the prominent issues that have framed his career: kinship, community, and self. The significance of David Warren Sabean's scholarship is reflected in original research contributed by former students and essays written by his contemporaries, demonstrating Sabean's impact on the discipline of history"--Provided by publisher